Changes in gene expressions of hypothalamic neuropeptides controlling feeding behaviors in bilateral nephrectomized rats. (15th October 2019) - Ueno, Hiromichi; Miyamoto, Tetsu; Sanada, Kenya; Nakazono, Kazutoshi; Tanaka, Kentaro; Nishimura, Haruki; Nishimura, Kazuaki; Sonoda, Satomi; Yoshimura, Mitsuhiro; Maruyama, Takashi; Serino, Ryota; Otsuji, Yutaka; et al.
Highlights: The mechanism by which anorexia occurs in kidney dysfunction is poorly understood. The changes in gene expressions of hypothalamic neuropeptides could induce anorexia. Food consumption decreased markedly in bilateral nephrectomized rats. Bilateral nephrectomy up-regulated the mRNA levels of CRH, POMC, and CART . Bilateral nephrectomy down-regulated the mRNA levels of AgRP, NPY, MCH, and Orexin . Abstract: Anorexia is one of the most widespread eating disorders that appears to contribute to malnutrition in patients with advanced kidney dysfunction. The changes of neuropeptides controlling feeding behaviors synthesized in the hypothalamus under several physiological condition could induce anorexia. While several mechanisms underlying uremic anorexia have been proposed, the changes of hypothalamic neuropeptides controlling feeding behaviors of uremic patients are poorly understood. The gene expressions of hypothalamic neuropeptides controlling feeding behaviors were evaluated after bilateral nephrectomy, which is a model of acute kidney dysfunction, by in situ hybridization histochemistry. Food consumption decreased markedly in bilateral nephrectomized rats. The mRNA levels of corticotrophin-releasing hormone, proopiomelanocortin, cocaine- and amphetamine-regulated transcript, which suppress feeding behavior, were significantly higher in bilateral nephrectomized rats than in sham-operated rats. On the other hand, the mRNA levels of Agouti-related peptide, neuropeptide Y, melanin-concentrating hormone, and orexin, which promote feeding behavior, were significantly lower in bilateral nephrectomized rats than in sham-operated rats. In addition, the plasma level of leptin, which has an anorexic effect, increased after bilateral nephrectomy. The results suggest that hypothalamic neuropeptides controlling feeding behaviors may be involved in the development of anorexia in bilateral nephrectomized rats. This report is the first step to elucidating the physiological mechanisms of anorexia in patients with kidney dysfunction.